Approaching the Land of Bliss Religious Praxis in the Cult of Amitābha - Getz, Daniel; Glassman, Hank; Jaffe, Richard M.; Jones, Charles B.; Kapstein, Matthew T.; Lewis, Todd T.; Payne, Richard K.; Payne, Richard K.; Rambelli, Fabio; Sanford, James H.; Stone, Jacqueline I.; Tanaka, Kenneth K. (University of Hawaii Press, 2003)
The discourse of Buddhist studies has traditionally been structured around texts and nations (the transmission of Buddhism from India to China to Japan). And yet, it is doubtful that these categories reflect in any significant way the organizing themes familiar to most Buddhists. It could be argued that cultic practices associated with particular buddhas and bodhisattvas are more representative of the way Buddhists conceive of their relation to tradition. This volume aims to explore this aspect of Buddhism by focusing on one of its most important cults, that of the Buddha Amitâbha. Approaching the Land of Bliss is a rich collection of studies of texts and ritual practices devoted to Amitâbha, ranging from Tibet to Japan and from early medieval times to the present. The cult of Amitâbha is identified as an integral part of Tibet's Mahayana Buddhist tradition in the opening essay by Matthew Kapstein.